MAKNA SIMBOLIK ACARA 7 BULANAN ETNIK MANDAR - Yunus, Nur Hafsah; Wahyuddin, Wahyuddin; Nurhikmah, Nurhikmah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2023)
The Seven Months Pregnancy Tradition this at cereemony fort children aged seveen month pregnant. The seveen-montly events this often done because this tradition is passed down from previous ancestors. This study aims to determine the implementation of the seven-monthly event that lives on the Mandar tribe in Mekkatta Village. The research is qualitative. Most of the data were collected through observation and interviews. Informants obtained as many as 5 people. Three people were present as guides for the Seven Monthly Program and two people who knew and understood the Seven Monthly program. Data collection techniques using purposive sampling technique. After interviews, participant observation, field notes, literature studies, documentation and internet searching. The results obtained indicate that symbols in the form of goods, objects, food that must be held during rituals are believed to bring good things for pregnant women and their families. In addition, the Mandar Ethnic community also connects these customs into the religion they believe in (still hoping for the pleasure of the One) so that the movements and speech that are carried out are in Arabic or in regional languages but are translations from Arabic whose sentences come from the Qur'an. This was done in order to make it easier for the Mandar Ethnic community to carry out the rituals they believed in.